Quantifying the pyroelectric and photovoltaic coupling series of ferroelectric films - Chaosheng Hu; Xingyue Liu; Huiyu Dan; Chong Guo; Maoyi Zhang; Chris R. Bowen; Ya Yang (Nature Communications)
Abstract The coupling of photovoltaic and pyroelectric effects is a common phenomenon in ferroelectric films and often results in coupling enhancements. Although the coupling effects of a variety of ferroelectric films have been examined in terms of improved performance, they have yet to be quantitatively ranked and assessed. Here, by taking the charge coupling factor, the Yang’s charge, and output energy as metrics to evaluate the coupling performance, a methodology is developed for evaluating the performance of a range ferroelectric films when the pyroelectric and photovoltaic effects are coupled. By experimentally measuring and quantitatively ranking the evaluation metrics, the influence of coupling effects on the output charge and the energy harvesting capabilities of various ferroelectric films can be readily visualized. In addition, the analysis of the underlying reasons for the coupling enhancement enables optimization of the methods to quantify the charge coupling factor. This work provides a unique reference for the selection of materials, optimization of performance, and energy harvesting for coupled ferroelectric film-based generators.